2016
DOI: 10.1371/journal.pone.0167034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Temporal Discrimination Threshold on Finger Movements of Parkinson’s Disease

Abstract: IntroductionSensory information is essential for the precise control of movement. Patients with Parkinson’s disease (PD) have higher-order sensory dysfunctions including prolonged temporal discrimination threshold (TDT). However, the impact of prolonged TDT on parkinsonian motor deficits is uncertain.MethodsThis study includes 33 PD patients and 24 healthy controls. TDT values were measured in the index finger. Using coin rotation task (CRT), dexterous finger movement was assessed. Using an inertial sensor, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Previous studies have proved that index finger tapping is significantly correlated with Lind-mark hand function assessment score and it plays an important role in hand function evaluation in patients with stroke (Zhang et al, 2014 ). The finger tapping is usually used to assess movement bradykinesia patients with Parkinson's disease patients (Lee et al, 2016 ). Moreover, a finger tapping test has been applied to measure performance validity in most of the standard neuropsychological evaluations (Axelrod et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that index finger tapping is significantly correlated with Lind-mark hand function assessment score and it plays an important role in hand function evaluation in patients with stroke (Zhang et al, 2014 ). The finger tapping is usually used to assess movement bradykinesia patients with Parkinson's disease patients (Lee et al, 2016 ). Moreover, a finger tapping test has been applied to measure performance validity in most of the standard neuropsychological evaluations (Axelrod et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the same line, STDT changes are present when dystonic features are not yet manifested in patients with increased blinking, a condition now considered to be a prodromal manifestation of blepharospasm [ 38 , 39 ]. Different from dystonia in other basal ganglia conditions, like Parkinson's disease, STDT changes reflect dopaminergic depletion [ 40 , 41 ] and disease progression [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the STDT in PD is normal at disease onset, which suggests that STDT abnormalities only appear when dopamine loss reaches a threshold that may be higher than that associated with the onset of motor symptoms ( 6 ), it may be considered as a marker of disease progression ( 6 ). Recent studies on PD ( 45 , 50 ) have suggested that an abnormal STDT might be involved in the development of parkinsonian motor deficits. The correlation between STDT values and variables that assess movement performance point to a possible link between altered STDT and motor disturbances in PD ( 8 , 45 ).…”
Section: Evidence On Actual and Illusory Tactile Information Processimentioning
confidence: 99%
“…Recent studies on PD ( 45 , 50 ) have suggested that an abnormal STDT might be involved in the development of parkinsonian motor deficits. The correlation between STDT values and variables that assess movement performance point to a possible link between altered STDT and motor disturbances in PD ( 8 , 45 ). In a study designed to investigate how STDT-related circuits interact with motor performance ( 50 , 106 ), we observed that the STDT increases at movement onset and returns to baseline values after 200 ms. We suggested that the increase in STDT during movement execution is likely to reflect mechanisms of sensory gating of tactile information that are irrelevant to the ongoing movement.…”
Section: Evidence On Actual and Illusory Tactile Information Processimentioning
confidence: 99%